Analisis Framing Pemberitaan Tragedi Kanjuruhan di Media Online - Dicky Irawan Taufiq; Hamid Arifin (Jurnal Komunikasi Massa, 2024)
The Kanjuruhan tragedy has captured the world's attention as one of the most heart- wrenching incidents in the history of global football, resulting in numerous casualties. This event is considered to have high news value by the media, as football is also one of the closest forms of entertainment to society. This research aims to analyze how the news framing is presented by the online media portal Narasi.tv through its program called "Buka Mata" The theoretical framework employed in this study is Peter L. Berger's theory of reality construction, which assumes that news is a reconstruction by the media of events that occur. The framing analysis used in this research adopts the model by Zhongdang Pan and Gerald M. Kosicki, comprising syntactic, script, thematic, and rhetorical structures. The researcher selected news for examination using purposive sampling, choosing three news articles within the timeframe of October 14, 2022, to March 16, 2023. Each of these articles presents the chronological development of the incident. The findings of this research indicate that Narasi.tv's framing in its reporting tends to blame the police as the party most responsible. The incompetence of the police in handling the crowd, particularly the use of tear gas, is highlighted, even though such usage is prohibited inside stadiums. Additionally, emphasis is placed on the court's judgment, which is perceived as not being impartial to the victims.